SAPHO Syndrome Complicated by Lesions of the Central Nervous System Successfully Treated with Brodalumab - Funabiki, Masahide; Tahara, Masayuki; Kondo, Seiko; Ayuzawa, Naho; Yanagida, Hidetoshi (Case Reports in Rheumatology, 2023)
Synovitis-acne-pustulosis-hyperostosis-osteitis (SAPHO) syndrome is a rare disease with an unknown entity that affects the skin and the peripheral and/or axial joints. Here, we report on a patient with SAPHO syndrome complicated by lesions of the central nervous system who was successfully treated with brodalumab, an IL-17 receptor blocker. He had been suffering from arthralgia in the wrists and knees as well as axial symptoms such as back pain and assimilation of cervical vertebrae. He had been treated with corticosteroid, salazosulfapyridine, methotrexate, and bisphosphonate; however, his peripheral and axial articular manifestation were intractable. Recently, biologics predominantly targeting TNF-α is employed for difficult-to-treat SAPHO cases; however, he had been complicated with the lesions of the central nervous system resembling multiple sclerosis (MS), an inflammatory demyelinating disorder in the central nervous system, for which application of TNF-α inhibitor is contraindicated. Alternatively, brodalumab was administered , which promptly ameliorated the articular manifestations without aggravating the lesions of the central nervous system. We propose that this type of IL-17 blockade could be an alternative therapy for DMARDs-resistant SAPHO syndrome.